Laminated structure, electronic device, electronic equipment and system
Patent Information
- Application Number
- JP2024508144
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-03-13
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2043-03-13
AI Technical Summary
【0008】 本発明の積層構造体、電子デバイス及び電子機器は、優れたヒステリシス特性を有する圧電体を含んでおり、本発明の製造方法によれば、前記圧電体、前記積層構造体、前記電子デバイス及び前記電子機器を工業的有利に得ることができるという効果を奏する。
Smart Images

Figure 0007651231000001 
Figure 0007651231000002 
Figure 0007651231000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric body, a laminated structure, an electronic device, an electronic apparatus, and a method for manufacturing these. [Background technology]
[0002] Lead zirconate titanate (Pb(Zr,Ti)O) has excellent piezoelectric and ferroelectric properties. 3 Thin films made of PZT (hereinafter referred to as PZT) are used in memory elements such as non-volatile memory (FeRAM), as well as in MEMS (Micro Electro Mechanical Systems) technology such as inkjet heads and acceleration sensors, taking advantage of their ferroelectric properties.
[0003] Recently, (200) oriented ZrO on a (100) oriented Si substrate has been developed. 2 It has been studied to form a (200)-oriented Pt film on a Pt film via a thin film or the like, thereby forming a piezoelectric film with good piezoelectric properties on the Pt film (Patent Document 1). However, conventional piezoelectric bodies are still not yet satisfactory in terms of adhesion and crystallinity at the interface, and for example, there are a relatively large number of defects, which makes them prone to imprinting, and there are also problems such as the polarization being easily lost when a voltage is applied in the reverse direction, making it difficult to obtain good hysteresis characteristics. As a result, the center of hysteresis of the polarization amount with respect to the applied voltage shifts to the negative applied voltage side, and the remnant polarization Pr at the applied voltage of 0 V is + is 20μC / cm 2 There has been a strong demand for a method capable of obtaining the above-mentioned highly reliable and excellent hysteresis characteristics and further improving the piezoelectric characteristics of a piezoelectric film. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-154015 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a piezoelectric body having excellent hysteresis characteristics, a laminate structure, an electronic device, and an electronic equipment each containing the piezoelectric body, and a manufacturing method by which these can be obtained in an industrially advantageous manner. [Means for solving the problem]
[0006] As a result of intensive research by the inventors in order to achieve the above object, it has been found that a method for manufacturing a piezoelectric film, comprising the steps of forming at least a compound film on a crystal substrate, subsequently laminating an epitaxial film containing a crystalline compound, laminating a single crystal film made of a conductive metal on the epitaxial film directly or via another layer, and then laminating a piezoelectric film on the single crystal film directly or via another layer, wherein the epitaxial film is formed by using a compound element in the compound film, and the piezoelectric film is laminated by a coating method, whereby the center of hysteresis of the polarization amount with respect to the applied voltage is shifted to the negative applied voltage side, and the remanent polarization Pr at the applied voltage of 0 V is reduced. + is 20μC / cm 2 The present inventors have found that the above-described piezoelectric material can be easily obtained, that the obtained piezoelectric material has excellent hysteresis characteristics free from problems such as imprinting, and have discovered that such a piezoelectric material and a method for manufacturing the same can solve all of the above-mentioned conventional problems at once. After obtaining the above findings, the present inventors conducted further studies and completed the present invention.
[0007] That is, the present invention relates to the following inventions. [1] The center of the hysteresis of the polarization amount with respect to the applied voltage has shifted to the negative applied voltage side, and the remanent polarization Pr + is 20μC / cm 2 The piezoelectric body is characterized by the above. [2] Remanent polarization Pr at the applied voltage of 0V + is 40μC / cm 2The piezoelectric body according to the above [1]. [3] Remanent polarization Pr at the applied voltage of 0V + and Pr - The absolute values of 2 The piezoelectric body according to the above [1]. [4] Remanent polarization Pr at the applied voltage of 0V + and Pr - and have approximately the same absolute value. [5] The piezoelectric material according to any one of [1] to [4] above, which is a PZT-based piezoelectric material. [6] A method for manufacturing a laminated structure, comprising forming at least a compound film on a crystal substrate, laminating an epitaxial film containing a crystalline compound, laminating a single crystal film made of a conductive metal on the epitaxial film directly or via another layer, and then laminating a piezoelectric film on the single crystal film directly or via another layer, wherein the epitaxial film is formed by using a compound element in the compound film, and the piezoelectric film is laminated by a coating method. [7] The manufacturing method according to [6], further comprising the steps of: using the compound element in the compound film; introducing a compound element gas; and depositing the epitaxial film in the presence of the compound element gas. [8] A laminated structure including at least a crystal substrate, an epitaxial film containing a crystalline compound, an electrode, and a piezoelectric body, wherein the piezoelectric body is the piezoelectric body described in any one of [1] to [5] above, and the epitaxial film is a laminated structure in which a compound element in a compound film laminated on the crystal substrate is incorporated into the crystalline compound. [9] The layered structure according to [8], wherein the epitaxial film constitutes a part or the whole of a buffer layer and is a substrate for crystal growth.
[10] A piezoelectric element including a laminated structure, characterized in that the laminated structure is the laminated structure described in [8] or [9] above.
[11] A method for manufacturing a piezoelectric element using a laminated structure, characterized in that the laminated structure is the laminated structure described in [8] or [9] above.
[12] An electronic device including a laminated structure, characterized in that the laminated structure is the laminated structure described in [8] or [9] above.
[13] The electronic device according to
[12] , which is a piezoelectric device.
[14] A method for producing an electronic device using a laminated structure, characterized in that the laminated structure is the laminated structure described in [8] or [9] above.
[15] An electronic device including an electronic device, characterized in that the electronic device is the electronic device described in
[13] or
[14] .
[16] A method for manufacturing an electronic device using a laminated structure or an electronic device, characterized in that the laminated structure is the laminated structure described in [8] or [9] above, and the electronic device is the electronic device described in
[13] or
[14] above.
[17] A system including an electronic device, characterized in that the electronic device is the electronic device described in
[15] .
[18] The laminate structure according to [8], further comprising: between the crystal substrate and the epitaxial film, one or more embedded layers each containing the constituent metal and the compound element of the epitaxial film and / or the crystal substrate, and / or a buried layer each containing the constituent metal and the compound element embedded in a portion of the crystal substrate.
[19] The laminate structure according to
[18] , further comprising an amorphous thin film between the crystal substrate and the epitaxial film, the amorphous thin film containing the constituent metal of the epitaxial film and the compound element, and / or one or more embedded layers embedded in a portion of the crystal substrate and containing the constituent metal of the epitaxial film and the compound element.
[20] The laminate structure according to
[18] , further comprising an amorphous thin film between the crystal substrate and the epitaxial film, the amorphous thin film containing the constituent metal of the epitaxial film and / or the crystal substrate and the compound element, and one or more embedded layers embedded in a portion of the crystal substrate and containing the constituent metal and the compound element.
[21] The layered structure according to any one of
[18] to
[20] , wherein the constituent metal comprises Hf.
[22] The layered structure according to any one of
[18] to
[21] , wherein the amorphous thin film has a thickness of 1 nm to 10 nm.
[23] The multilayer structure according to any one of
[18] to
[22] , wherein the embedded layer has a cross-sectional shape of a substantially inverted triangle.
[24] An electronic device, an electronic equipment, or a system including a laminate structure, characterized in that the laminate structure is the laminate structure according to any one of
[18] to
[23] above. Effect of the Invention
[0008] The laminated structure, electronic device, and electronic equipment of the present invention contain a piezoelectric material having excellent hysteresis characteristics, and the manufacturing method of the present invention has the effect of making it possible to obtain the piezoelectric material, the laminated structure, the electronic device, and the electronic equipment in an industrially advantageous manner. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of an example of a preferred embodiment of a precursor of a laminated structure of the present invention. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of another preferred embodiment of the laminated structure of the present invention. [Diagram 3] 1A to 1C are diagrams illustrating an example of an oxide film forming step in a preferred method for producing a laminated structure of the present invention. [Figure 4] 1A to 1C are diagrams illustrating an example of an epitaxial film formation step in a preferred method for producing a laminated structure of the present invention. [Diagram 5]1 shows cross-sectional STEM images observed in the examples. [Figure 6] 1 shows cross-sectional STEM images observed in the examples. [Figure 7] 1 shows STEM images observed in the examples. [Figure 8] 1 shows STEM images observed in the examples. [Figure 9] 1 is a diagram illustrating a preferred embodiment of a MEMS transducer according to the present invention. [Figure 10] FIG. 1 is a schematic diagram showing an example of a cross-sectional view of a portion of a wafer provided with a piezoelectric actuator, as a suitable application example of the present invention to a fluid discharge device. [Figure 11] 1 is a diagram showing hysteresis curves measured in the examples, with the vertical axis representing the remanent polarization and the horizontal axis representing the applied voltage. [Figure 12] FIG. 2 is a diagram showing the results of XPS measurement in an example. [Figure 13] FIG. 2 is a diagram showing the results of XPS measurement in an example. [Figure 14] FIG. 2 is a schematic diagram showing a film forming apparatus preferably used in the examples. [Figure 15] 1 shows a cross-sectional STEM image measured in an example. [Figure 16] 1 shows a STEM image measured in an example. [Figure 17] 1 shows a STEM image of a buried layer measured in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the piezoelectric body of the present invention, the center of hysteresis of the polarization amount with respect to the applied voltage is shifted to the negative applied voltage side, and the remanent polarization Pr + is 20μC / cm 2 In the present invention, it is preferable that the center of the hysteresis is shifted to the positive applied voltage side by 10 to 50 V, and the residual polarization Pr at the applied voltage of 0 V is + is 40μC / cm 2In the present invention, the residual polarization Pr at the applied voltage of 0 V is preferably equal to or greater than 1 V. + and Pr - However, it is preferable that the absolute values of the remanent polarization Pr and the remanent polarization Pr are substantially the same. + and Pr - The absolute values of the remanent polarization Pr at the applied voltage of 0 V are completely the same, or the difference between them is within 5% (preferably within 1%). + and Pr - The absolute values of are 20μC / cm 2 It is preferable that the temperature is 40 μC / cm or more. 2 More preferably, it is equal to or greater than this.
[0011] The piezoelectric body can be easily obtained by forming at least a compound film on a crystal substrate, then laminating an epitaxial film containing a crystalline compound, and then laminating a single crystal film made of a conductive metal on the epitaxial film directly or through another layer, and then laminating a piezoelectric film on the single crystal film directly or through another layer, by forming the epitaxial film using a compound element in the compound film, and laminating the piezoelectric film by a coating method. The crystalline compound is not particularly limited and may be a known crystalline compound, but in the present invention, the crystalline compound is preferably a metal compound, and the metal of the metal compound may also be a known metal. Examples of the metal include D block metals in the periodic table. The compound of the metal compound may also be a known compound, and examples of the compound in the crystalline compound include oxides, nitrides, oxynitrides, sulfides, oxysulfides, borides, oxyborides, carbides, oxycarbides, borocarbides, boronitrides, borosulfides, carbonitrides, carbosulfides, and carboborides. In the present invention, oxides or nitrides are preferred because, for example, they can provide better stress relaxation and warpage reduction in heteroepitaxial growth as a buffer layer, and can further provide better electrical properties (particularly the interface between the conductor layer and the insulating layer). In addition, the crystalline compound is preferably a crystalline oxide, the compound film is preferably an oxide film, and the compound element is preferably oxygen. In the present invention, the crystalline compound is preferably a crystalline nitride, the compound film is preferably a nitride film, and the compound element is preferably nitrogen.
[0012] FIG. 1 shows a preferred example of the precursor of the laminated structure. In the precursor of the laminated structure of FIG. 1, an epitaxial layer 3 is laminated on a crystal substrate 1 using an oxide film 2, and a second epitaxial layer 4 is further laminated on the epitaxial layer 3. In this specification, the terms "film" and "layer" may be interchanged depending on the case or situation. In addition, although oxides are given as preferred examples of the laminated structure, the present invention is not limited to these preferred examples, and the present invention can also be suitably applied to various compounds such as nitrides.
[0013] The precursor can be easily produced, for example, as shown in Fig. 3, by forming an oxide film 2 of the crystal substrate 1 on the crystal substrate 1, and then using oxygen in the oxide film 2 to form an epitaxial film 3 made of a crystalline oxide on the crystal substrate 1, as shown in Fig. 4. In the present invention, the precursor may have the oxide film 2 on the crystal substrate 1, or the oxide film 2 may disappear when the epitaxial film 3 is formed by taking in all of the oxygen in the oxide film 2. Each of these will be described in more detail below, but the present invention is not limited to these specific examples.
[0014] The crystal substrate (hereinafter, simply referred to as "substrate") is not particularly limited as long as the object of the present invention is not hindered, such as the substrate material, and may be a known crystal substrate. It may be an organic compound or an inorganic compound. In the present invention, it is preferable that the crystal substrate contains an inorganic compound. In the present invention, it is preferable that the substrate has crystals on a part or all of the surface, more preferably a crystal substrate having crystals on all or a part of the main surface on the crystal growth side, and most preferably a crystal substrate having crystals on the entire main surface on the crystal growth side. The crystal is not particularly limited as long as the object of the present invention is not hindered, and the crystal structure is not particularly limited, but it is preferable that it is a cubic, tetragonal, trigonal, hexagonal, orthorhombic, or monoclinic crystal, and more preferably a crystal oriented in (100) or (200). In addition, the crystal substrate may have an off angle, and examples of the off angle include an off angle of 0.2° to 12.0°. Here, the "off angle" refers to the angle between the substrate surface and the crystal growth surface. The shape of the substrate is not particularly limited as long as it is plate-like and serves as a support for the epitaxial film. It may be an insulating substrate or a semiconductor substrate, but in the present invention, the substrate is preferably a Si substrate, more preferably a crystalline Si substrate, and most preferably a crystalline Si substrate oriented in (100). In addition to the Si substrate, examples of the substrate material include one or more metals belonging to Groups 3 to 15 of the periodic table or oxides of these metals. The shape of the substrate is not particularly limited, and may be an approximately circular shape (e.g., a circular shape, an elliptical shape, etc.) or a polygonal shape (e.g., a triangular shape, a square shape, a rectangular shape, a pentagonal shape, a hexagonal shape, a heptagonal shape, an octagonal shape, a nonagonal shape, etc.), and various shapes can be suitably used. In addition, in the present invention, a large-area substrate can be used, and the area of the epitaxial film can be increased by using such a large-area substrate.
[0015] In the present invention, the crystal substrate preferably has a flat surface, but it is also preferable that the crystal substrate has an uneven shape on a part or all of the surface, since this improves the quality of the crystal growth of the epitaxial film. The crystal substrate having the uneven shape may have an uneven portion consisting of a concave or convex portion formed on a part or all of the surface, and the uneven portion is not particularly limited as long as it is composed of a convex or concave portion, and may be an uneven portion consisting of a convex portion, an uneven portion consisting of a concave portion, or an uneven portion consisting of a convex portion and a concave portion. The uneven portion may be formed of regular convex portions or concave portions, or may be formed of irregular convex portions or concave portions. In the present invention, it is preferable that the uneven portion is formed periodically, and it is more preferable that the uneven portion is patterned periodically and regularly. The shape of the uneven portion is not particularly limited, and examples thereof include a stripe shape, a dot shape, a mesh shape, and a random shape, but in the present invention, a dot shape or a stripe shape is preferable, and a dot shape is more preferable. In addition, when the unevenness is patterned periodically and regularly, the pattern shape of the unevenness is preferably a polygonal shape such as a triangle, a quadrangle (for example, a square, a rectangle, or a trapezoid), a pentagon, or a hexagon, a circle, or an ellipse. In addition, when the unevenness is formed in a dot shape, the lattice shape of the dots is preferably a lattice shape such as a square lattice, an oblique lattice, a triangular lattice, or a hexagonal lattice, and more preferably a triangular lattice shape. The cross-sectional shape of the concave or convex part of the unevenness is not particularly limited, but examples thereof include a U-shape, a U-shape, an inverted U-shape, a wave shape, or a polygonal shape such as a triangle, a quadrangle (for example, a square, a rectangle, or a trapezoid), a pentagon, or a hexagon. In addition, the thickness of the crystal substrate is not particularly limited, but is preferably 50 to 2000 μm, and more preferably 100 to 1000 μm.
[0016] The oxide film is not particularly limited as long as it is an oxide film capable of incorporating oxygen atoms into the epitaxial film, and usually includes an oxide material. The oxide material is not particularly limited as long as it does not impede the object of the present invention, and may be a known oxide material. Examples of the oxide material include oxides of metals or semimetals. In the present invention, it is preferable that the oxide film includes the oxide material of the crystal substrate, and examples of such oxide films include a thermal oxide film and a natural oxide film of the crystal substrate. In addition, in the present invention, the oxide film may be a sacrificial layer in which a part or all of the film disappears or is destroyed when oxygen atoms are incorporated, and in the present invention, it is preferable that the oxide film is an oxygen supply sacrificial layer in which oxygen atoms are incorporated and the oxide film itself disappears during the crystal growth of the epitaxial layer. In addition, the oxide film may be patterned, for example, in a striped, dotted, meshed, or random pattern. The thickness of the oxide film is not particularly limited, but is preferably more than 1 nm and less than 100 nm.
[0017] The epitaxial layer is not particularly limited as long as it includes an epitaxial film incorporating oxygen atoms from the oxide film. The "epitaxial film incorporating oxygen atoms from the oxide film" means that oxygen atoms from the oxide film are taken by the epitaxial film during the crystal growth of the epitaxial film. The epitaxial film is not particularly limited as long as it is an epitaxial film that has been crystal-grown by incorporating oxygen atoms from the oxide film, but in the present invention, it is preferable that it includes a metal or a metal oxide. The metal is preferably, for example, one or more metals belonging to the d block of the periodic table. The metal oxide is preferably, for example, one or more oxides of metals belonging to the d block of the periodic table. In the present invention, it is preferable that the epitaxial film includes a dielectric material. In addition, in the present invention, it is preferable that the epitaxial film includes a neutron absorbing material. The neutron absorber may be a known neutron absorber, and in the present invention, by using such a neutron absorber to capture oxygen from the oxide film, it is possible to improve adhesion, crystallinity, and further the properties of the functional film. A suitable example of the neutron absorber is hafnium (Hf). The epitaxial layer may be composed of one or more types of epitaxial films, and in the present invention, it is preferable that the epitaxial layer includes two or more types of the epitaxial films. More specifically, for example, it is preferable that a second epitaxial film having a composition different from that of the epitaxial film is laminated on the epitaxial film directly or via another layer. By stacking in this manner, the first epitaxial layer can be regularly transformed at the interface between the epitaxial layer (hereinafter also referred to as the "first epitaxial layer") and the second epitaxial layer so that the lattice constant thereof becomes approximately the same as that of the second epitaxial layer.As a preferred example of the regular transformation, for example, a transformation in which the shape is transformed into a mountain-valley structure is given. In the present invention, it is preferable that the angles formed by the adjacent vertices and bottoms of the mountain-valley structure are different from each other, and it is more preferable that each of the angles is within the range of 30° to 45°. Here, the epitaxial layer usually has a first crystal face and a second crystal face, and since the transformation may cause a lattice constant difference between the first crystal face and the second crystal face, it is preferable that the lattice constant difference between the first crystal face and the second crystal face is within the range of 0.1% to 20%. In the present invention, since the first crystal face can be made substantially the same as the lattice constant of the second epitaxial film, it is easy to realize that the lattice constant difference between the first epitaxial layer and the second epitaxial layer is within the range of 0.1% to 20%.
[0018] In the present invention, it is more preferable that the epitaxial film is a dielectric and the second epitaxial film is an electrode. By using the second epitaxial layer as an electrode, not only can the adhesion and crystallinity at the interface be improved, but also, for example, the characteristics of the element can be improved. In addition, according to the present invention, when the second epitaxial layer is made of a single crystal film of a conductive metal, a large-area defect-free film can be easily obtained, and not only the function as an electrode but also the characteristics of the element can be improved. The conductive metal is not particularly limited as long as it does not impede the object of the present invention, and examples thereof include gold, silver, platinum, palladium, silver-palladium, copper, nickel, and alloys thereof, but in the present invention, it is preferable that it contains platinum. In addition, in the present invention, according to the above-mentioned manufacturing method, it is preferable to obtain a film having a thickness of 100 nm or more. 2 A defect-free single crystal film can be obtained as an electrode with an area of 1000 nm or more. 2 A defect-free single crystal film can be easily obtained with the above area. Also, a single crystal film having a thickness of preferably 100 nm or more can be easily obtained as an electrode.
[0019] In the present invention, it is preferable that a third epitaxial film and / or a fourth epitaxial film having a composition different from that of the second epitaxial film is laminated on the second epitaxial film directly or via another layer. Fig. 2 shows a preferred example of a laminated structure in which the third epitaxial layer 5 and the fourth epitaxial layer 6 are laminated on the second epitaxial layer 4. In the laminated structure of Fig. 2, a first epitaxial layer 3 is laminated on a crystal substrate 1 using an oxide film, and further, a second epitaxial layer 4 is laminated on the first epitaxial layer 3, a third epitaxial layer 5 is laminated on the second epitaxial layer 4, and a fourth epitaxial layer 6 is laminated on the third epitaxial layer 5. The third epitaxial film in the third epitaxial layer is preferably a dielectric, a semiconductor, or a conductor, more preferably a dielectric, and most preferably a piezoelectric. The fourth epitaxial film in the fourth epitaxial layer is preferably a dielectric, a semiconductor, or a conductor, more preferably a dielectric, and most preferably a piezoelectric. The thickness of each of the epitaxial films is not particularly limited, but is preferably 10 nm to 1000 μm, and more preferably 10 nm to 100 μm.
[0020] The precursor can be easily obtained by laminating an epitaxial layer on a crystal substrate via at least an oxide film, and forming the epitaxial film using oxygen atoms in the oxide film at 350° C. to 700° C. If the temperature is within the range of 350° C. to 700° C., the oxygen atoms in the oxide film can be more easily incorporated into the epitaxial film to cause crystal growth.
[0021] In the present invention, it is preferable to form the epitaxial film by using oxygen gas after using oxygen atoms in the oxide film, and the film formation rate is improved by forming the epitaxial film in this way. Also, by forming the film in this way, a laminated structure in which an epitaxial film containing a crystalline compound is laminated on a crystal substrate, and a laminated structure having an amorphous thin film containing a metal constituting the epitaxial film and / or the crystal substrate and a compound element of the crystalline compound and / or one or more buried layers containing the metal constituting the epitaxial film and the compound element, which are embedded in a part of the crystal substrate, can be easily obtained. Also, in the present invention, it is preferable to form an amorphous thin film containing a metal constituting the epitaxial film and a compound element of the crystalline compound and / or one or more buried layers containing the metal constituting the epitaxial film and the compound element, which are embedded in a part of the crystal substrate, between the crystal substrate and the epitaxial film, because the crystallinity of the epitaxial film is improved. In the present invention, it is preferable that an amorphous thin film containing a constituent metal of the epitaxial film and / or the crystal substrate and a compound element of the crystalline compound, and one or more buried layers containing the constituent metal and the compound element are provided between the crystal substrate and the epitaxial film, since the functionality of the epitaxial film can be further improved. In the present invention, it is preferable that the constituent metal contains Hf, since it further promotes stress relaxation and can further realize multi-stage stress relaxation. In the present invention, it is preferable that the thickness of the amorphous thin film is 1 nm to 10 nm, since it can further improve the crystallinity of the epitaxial film, and an amorphous thin film with such a preferable thickness can be easily obtained by the preferred manufacturing method of the present invention. In the present invention, it is preferable that the shape of the buried layer has a cross-sectional shape of an approximately inverted triangle, since it can further improve the functionality of the epitaxial film. These preferable laminated structures are:This can be easily achieved by appropriately adjusting the thickness of the oxide film and the timing of introducing the oxygen gas.
[0022] As the lamination means used in laminating the epitaxial film, the deposition means for the epitaxial film is usually preferably used, and the deposition means may be a known deposition means. In the present invention, the deposition means is preferably vapor deposition or sputtering, and more preferably vapor deposition.
[0023] The lamination means used in laminating the third epitaxial film or the fourth epitaxial film is usually a coating method. Examples of the coating method include spin coating, dip coating, roll coating, and spraying, and in the present invention, spin coating is preferred. By laminating in this manner, the center of hysteresis of the polarization amount with respect to the applied voltage is shifted to the negative applied voltage side, and the remanent polarization Pr at the applied voltage of 0V is + is 20μC / cm 2 The present invention also includes a laminated structure including at least the crystal substrate, the epitaxial film, the electrode, and the piezoelectric body, in which oxygen atoms in an oxide film laminated on the crystal substrate are incorporated into the crystalline oxide, and in the laminated structure of the present invention, the epitaxial film preferably constitutes a part or the whole of a buffer layer and is a substrate for crystal growth.
[0024] The laminated structure obtained as described above is suitably used in electronic devices according to a conventional method. For example, the laminated structure can be connected to a power source or an electric / electronic circuit as a piezoelectric element, and mounted on a circuit board or packaged to form various electronic devices. In the present invention, the electronic device is preferably a piezoelectric device, and can be used as a piezoelectric device in electronic devices such as inkjet printer heads, microactuators, gyroscopes, and motion sensors. In addition, for example, if an amplifier and a rectifier circuit are connected and packaged, it can be used as various sensors such as magnetic sensors. It can also be applied to constant voltage driven memories, and for example, if a storage element and a rectifier power management circuit are connected, it becomes an energy conversion device (energy harvester) that generates power from an external magnetic field or vibration. The energy conversion device is incorporated and used in a power supply system or a wearable terminal (earphone / hearable device, smart watch, smart glasses (eyeglasses), smart contact lenses, cochlear implants, cardiac pacemakers, etc.). In the present invention, the laminated structure is preferably used in, for example, smart glasses, AR headsets, MEMS mirrors for LiDAR systems, piezoelectric MEMS ultrasonic transducers (PMUTs) for advanced medical applications, and piezo heads for commercial and industrial 3D printers.
[0025] The electronic device is suitably used in electronic devices in the usual manner, and can be applied to various electronic devices other than the above-mentioned electronic devices, and more specifically, suitable examples include liquid ejection heads, liquid ejection devices, vibration wave motors, optical devices, vibration devices, imaging devices, piezoelectric acoustic parts, audio playback devices having the piezoelectric acoustic parts, audio recording devices, mobile phones, various information terminals, and the like.
[0026] Furthermore, the electronic device is also applied to a system in the usual manner, and an example of such a system is a sensor system. EXAMPLES
[0027] Example 1 The crystal growth surface side of the Si substrate (100) was treated by RIE, and then heated in the presence of oxygen to form a thermal oxide film. Then, without using oxygen, a metal from the deposition source was thermally reacted with oxygen in the oxide film on the Si substrate by vapor deposition to form a single crystal of crystalline metal oxide on the Si substrate. Next, oxygen was introduced, the temperature was lowered, and the pressure was increased, and a single crystal film of crystalline metal oxide was formed by vapor deposition. The conditions of the vapor deposition method during this film formation were as follows: Vapor deposition source: Hf, Zr Voltage: 3.5~4.75V Pressure: 3×10 -2 ~6×10 -2 Pa Substrate temperature: 450~700℃
[0028] Next, a platinum (Pt) metal film was formed as a conductive film on the single crystal film of the crystalline metal oxide by sputtering under the following conditions. Equipment: ULVAC sputtering equipment QAM-4 Pressure: 1.20×10 -1 Pa Target: Pt Power: 100W(DC) Thickness: 100nm Substrate temperature: 450~600℃
[0029] Next, an SRO film was formed on the conductive film by sputtering under the following conditions. Equipment: ULVAC sputtering equipment QAM-4 Power: 150W(RF) Gas: Ar Pressure: 1.8Pa Substrate temperature: 600℃ Thickness: 20nm
[0030] Next, a Pb(Zr 0.52 Ti 0.48 )O 3 The film (PZT film) was formed by a coating method under the following conditions.
[0031] Lead acetate was used as the raw material for Pb, zirconyl nitrate was used as the raw material for Zr, and titanium isopropoxide was used as the raw material for Ti. The raw materials for Pb, Zr, and Ti were mixed to a composition ratio of Pb:Zr:Ti=100+δ:52:48, and the solvent was pure water in consideration of the solubility of the raw materials, with acetic acid added to control hydrolysis. Furthermore, ethanol (0.5-3.0 mol per 1 mol of PZT) in which polyvinylpyrrolidone powder had been mixed and dissolved was added to adjust the viscosity. Finally, an appropriate amount of 2n-butoxyethanol was mixed to adjust the wettability during application, and a sol-gel solution was prepared as the raw material solution.
[0032] Next, the prepared sol-gel solution was dropped onto a substrate and rotated at 2000 rpm for 1 minute to spin coat (apply) the sol-gel solution onto the substrate, forming a film containing the precursor. The substrate was then placed on a hot plate at 150°C, and then placed on a hot plate at 350°C to evaporate the solvent and dry the film. This process was repeated five times to stack five layers under the same conditions, and then oxygen (O 2 The precursor was oxidized and crystallized by heat treatment at 650 °C for 3 minutes in a Pb(Zr 0.52 Ti 0.48 )O 3 A film (PZT film) was produced. The total film thickness at this time was 10 μm.
[0033] 5 and 6 show cross-sectional STEM images of the obtained laminated structure. From FIG. 6, it can be seen that a very good laminated structure has been obtained. In particular, from FIG. 5, it can be seen that a regular mountain-valley structure is provided at the interface between the single crystal film of the crystalline metal oxide and the conductive film, and the angles formed by the adjacent vertices and bottom points of the mountain-valley structure are different within the range of 30° to 45°. Furthermore, X-ray crystal lattice images of the conductive film are shown in FIG. 7 and FIG. 8. From FIG. 7 and FIG. 8, it can be seen that a defect-free large-area conductive film is obtained, and that these have a good effect on the electrode characteristics and the piezoelectric characteristics of the piezoelectric film laminated thereon. Furthermore, the crystals of the crystal substrate of the laminated structure, the single crystal film of the crystalline metal oxide, and the conductive film were measured using an X-ray diffraction device. FIG. 12 shows the results of XPS measurement. As is clear from FIG. 12, a (Hf, Zr)O film having good crystallinity was formed on a Si crystal substrate. 2 A Pt single crystal film and a Pt film were formed.
[0034] Example 2 A platinum (Pt) metal film was formed as a conductive film on the single crystal film of the crystalline metal nitride in the same manner as in Example 1, except that nitrogen gas was used instead of oxygen gas. Then, the crystal substrate of the laminated structure, the single crystal film of the crystalline metal nitride, and the conductive film were each measured using an X-ray diffraction device. FIG. 13 shows the results of the XPS measurement. As is clear from FIG. 13, a (Hf, Zr)N film and a Pt single crystal film having good crystallinity were formed on the Si crystal substrate. When measured by a four-terminal method, the obtained single crystal film of the crystalline metal nitride had good conductivity.
[0035] The deposition apparatus used in Example 1 is shown in Fig. 14. The deposition apparatus in Fig. 14 includes at least metal sources 101a-101b in a crucible, earths 102a-102h, ICP electrodes 103a-103b, cut filters 104a-104b, DC power sources 105a-105b, RF power sources 106a-106b, lamps 107a-107b, Ar source 108, reactive gas source 109, power source 110, substrate holder 111, substrate 112, cut filter 113, ICP ring 114, vacuum chamber 115, and rotation shaft 116. The ICP electrodes 103a-103b in Fig. 14 have a substantially concave curved shape or a parabolic shape curved toward the center of substrate 112.
[0036] As shown in Fig. 14, the substrate 112 is fixed on the substrate holder 111. Next, the rotating shaft 116 is rotated using the power supply 110 and a rotating mechanism (not shown) to rotate the substrate 112. The substrate 112 is heated by the lamps 107a-107b, and the inside of the vacuum chamber 115 is evacuated to a vacuum or reduced pressure by a vacuum pump (not shown). Thereafter, Ar gas is introduced from the Ar source 108 into the vacuum chamber 115, and argon plasma is formed on the substrate 112 using the DC power supplies 105a-105b, the RF power supplies 106a-106b, the ICP electrodes 103a-103b, the cut filters 104a-104b, and the earths 102a-102h, thereby cleaning the surface of the substrate 112.
[0037] Ar gas is introduced into the vacuum chamber 115, and a reactive gas is introduced using a reactive gas source 109. At this time, lamps 107a to 107b, which are lamp heaters, are alternately turned on and off, so that a crystal growth film of better quality can be formed.
[0038] The laminated structure obtained in the same manner as in Example 1 was subjected to STEM analysis. The results are shown in Figs. 15 to 17. From Fig. 15, it can be seen that an embedded layer 1004 is formed between the crystal substrate 1011 and the epitaxial layer 1001, and further, amorphous layers 1002 and 1003 are formed. From Fig. 16, it can be seen that the first amorphous layer 1002 on the crystal substrate 1011 contains Si of the crystal substrate and Zr, which is a constituent metal of the epitaxial layer 1001. From Fig. 17, it can be seen that the embedded layer 1004 has a cross-sectional shape of a substantially inverted triangle, and is an oxide containing Hf and Si.
[0039] (Examples) Examples of applications of the obtained laminated structure will be described in more detail below with reference to the drawings, but the present invention is not limited to these examples. In the present invention, unless otherwise specified, a piezoelectric device or the like can be manufactured from the laminated structure by using known means.
[0040] 9 shows an embodiment of an acoustic MEMS transducer constituting a MEMS microphone in which the laminated structure of the present invention is preferably used. The MEMS transducer can constitute an acoustic emission device (for example, a speaker, etc.).
[0041] The MEMS microphone configured with the acoustic MEMS transducer in FIG. 9 shows a cantilever type MEMS microphone, and includes a Si substrate 21 having two cantilever beams 28A, 28B and a cavity 30. Each of the cantilever beams 28A, 28B is fixed to the substrate 21 at each end, and a gap 9 is provided between the cantilever beams 8A, 8B. The cantilever beams 8A, 8B are formed, for example, by a laminated structure including a plurality of piezoelectric layers (PZT films) 26a, 26b, which are alternated with a plurality of electrode layers, i.e., Pt films 24a, 24b, 24c and SRO films 25a, 25b, 25c, 25d. The dielectric layer (single crystal film of crystalline oxide) 23 electrically insulates the cantilever beams 8A, 8B from the crystal substrate 21. In FIG. 9, the dielectric layer (single crystal film of crystalline oxide) 23 is provided with a neutron absorbing material (e.g., HfO 2 or its mixed crystal) is used, and SiO 2 Compared to cases where SiN or the like is used, it has excellent adhesion to the Si substrate and crystallinity, and furthermore, it has excellent piezoelectric properties and durability.
[0042] FIG. 10 shows an example of application to a printing application in which the laminated structure of the present invention is preferably used, particularly to a fluid discharge device that can be used in the form of an inkjet printhead. Specifically, a cross-sectional view of a portion of a wafer having a piezoelectric actuator including Pt films 34a, 34b and SRO films 35a, 35b as electrode layers and a PZT film 36 as a piezoelectric film is shown. In addition to the piezoelectric actuator, the wafer of FIG. 10 has a chamber 41 for containing a fluid. The chamber 41 is configured to take in a fluid from a tank (not shown) through a flow path 40. The wafer of FIG. 10 also includes a Si substrate 31, on which a dielectric layer (single crystal film of a crystalline oxide) 33 is provided as a first epitaxial layer, facing the chamber 41. In FIG. 10, a neutron absorbing material (e.g., HfO 2 or its mixed crystal) is used, and SiO 2Compared with the case where SiN or the like is used, the single crystal film 33 of the crystalline oxide has excellent adhesion to the Si substrate and crystallinity, and further has excellent piezoelectric properties and durability. The single crystal film 33 of the crystalline oxide has, for example, a quadrangular shape in a top view (not shown), and the shape may be, for example, any of a square, a rectangle, a rectangle with rounded corners, a parallelogram, etc.
[0043] A Pt film 34a, an SRO film 35a, a piezoelectric film (PZT film) 36, an SRO film 35b, and a Pt film 34b are laminated in this order on the single crystal film 33 of the crystalline oxide to form a piezoelectric actuator. The piezoelectric actuator further includes an insulating film 37 extending over the electrodes 34a and 35a, the piezoelectric film 36, and the electrodes 34b and 35b. The insulating film 37 includes a dielectric material used for electrical insulation, which may be a known dielectric material, for example, SiO 2 layer, SiN layer or Al 2 O 3The insulating layer may be a layer. The thickness of the insulating layer containing an insulating film as a constituent material is not particularly limited, but is preferably between about 10 nm and about 10 μm. The conductive path 39 is provided on the insulating layer (insulating film) 37, and contacts the electrodes 34a and 35a and the electrodes 34b and 35b, respectively, to enable selective access during use. The constituent material of the conductive path may be a known conductive material, and a suitable example of such a conductive material is aluminum (Al). The passivation layer 42 is provided on the insulating layer 37, the electrodes 34b and 35b, and the conductive path 39. The passivation layer 42 may be made of a dielectric material used for passivation of the piezoelectric actuator, and the dielectric material is not particularly limited, and may be a known dielectric material. Suitable examples of the dielectric material include SiN and SiON (silicon oxynitrate). The thickness of the passivation layer is not particularly limited, but is preferably between about 0.1 μm and about 3 μm. Similarly, a conductive pad 38 is provided along the piezoelectric actuator and is electrically connected to a conductive path 39. The passivation layer 42 functions as a barrier layer that protects the piezoelectric body from moisture and the like. [Industrial Applicability]
[0044] The piezoelectric body and the laminated structure of the present invention are preferably used as electronic devices such as piezoelectric devices, and are preferably used in electronic equipment, sensor systems, and the like. [Explanation of symbols]
[0045] 1. Crystal Substrate 2. Oxide film 3 (First) Epitaxial Layer 4 Second epitaxial layer 5. Third epitaxial layer 6 Fourth epitaxial layer 11. Silicon substrate 13 Single crystal film of crystalline oxide 14 Conductive film 15 SRO membrane 16 PZT membrane 21 Crystalline substrate (Si substrate) 23 (First) epitaxial layer (single crystal film of crystalline oxide) 24a Second epitaxial layer (Pt film) 24b Sixth epitaxial layer (Pt film) 24c 10th epitaxial layer (Pt film) 25a Third epitaxial layer (SRO film) 25b Fifth epitaxial layer (SRO film) 25c Seventh epitaxial layer (SRO film) 25d 9th epitaxial layer (SRO film) 26a Fourth epitaxial layer (PZT film) 26b Eighth epitaxial layer (PZT film) 28A Cantilever Beam 28B Cantilever beam 29 Gap 30 cavities 31 Crystalline substrate (Si substrate) 33 (First) epitaxial layer (single crystal film of crystalline oxide) 34a Second epitaxial layer (Pt film) 34b Sixth epitaxial layer (Pt film) 35a Third epitaxial layer (SRO film) 35b Fifth epitaxial layer (SRO film) 36 Fourth epitaxial layer (PZT film) 37 Insulating Film 38 Conductive Pad 39 Conductive Path 40 Flow Path 41 Chamber 42 Passivation Layer 101a~101b Metal source 102a~102j Earth 103a~103b ICP electrode 104a~104b Cut Filter 105a~105b DC power supply 106a~106b RF power supply 107a~107b Lamps 108 Ar source 109 Reactive Gas Sources 110 Power supply 111 PCB Holder 112 Substrate 113 Cut Filter 114 ICP Ring 115 Vacuum chamber 116 Rotational Axis 1001 Epitaxial layer 1002 First amorphous layer 1003 Second amorphous layer 1004 Buried Layer 1011 Board
Claims
1. A laminated structure having at least a crystalline substrate which is a Si substrate, an epitaxial film which is a metal oxide containing Hf and Zr, an electrode, and a piezoelectric body, a first amorphous layer formed between the crystal substrate and the epitaxial film and containing Zr and Si; a second amorphous layer formed between the first amorphous layer and the epitaxial film, the second amorphous layer including Hf, Zr and Si; one or more buried layers embedded in a portion of the crystal substrate and containing Hf and Si; having The center of hysteresis of the amount of polarization with respect to the applied voltage of the piezoelectric body is shifted to the negative applied voltage side, and the remanent polarization Pr + is 20 μC / cm 2 That's all. The buried layer buried in a portion of the crystal substrate has a cross-sectional shape of a substantially inverted triangle.
2. The electrode is formed on the epitaxial film, a regular peak-valley structure is provided at an interface between the epitaxial film and the electrode; 2. The laminated structure according to claim 1, wherein the angles formed by adjacent vertices and bottoms of the peak-valley structure are different from each other within a range of 30° to 45°.
3. A laminated structure as described in claim 1, wherein a peak-valley structure is provided at the interface between the second amorphous layer and the epitaxial film.
4. The remanent polarization Pr at the applied voltage of 0 V + is 40 μC / cm 2 The laminated structure according to claim 1 .
5. The remanent polarization Pr at the applied voltage of 0 V + and Pr - The absolute values of 2 The laminated structure according to claim 1 .
6. The remanent polarization Pr at the applied voltage of 0 V + and Pr - The laminated structure according to claim 1 , wherein each of the above has substantially the same absolute value.
7. The laminated structure described in claim 1, wherein the piezoelectric material is a PZT-based piezoelectric material.
8. An electronic device, electronic equipment, or system including a laminate structure, characterized in that the laminate structure is the laminate structure according to any one of claims 1 to 7.
Citation Information
Patent Citations
Piezoelectric device, liquid discharge head, ferroelectric device, electronic equipment, and these manufacturing methods
JP2004165243A
Piezoelectric ceramic and method of manufacturing the same
JP2008069051A
Raw material powder for film deposition, film structure, method for producing them and piezoelectric element
JP2008100887A
Ferroelectric ceramic and method for manufacturing the same
JP2015154015A
Film structure and manufacturing method thereof
JP2018081975A